Monetary policy and inflation expectations: Impact and causal analysis of heterogeneous economic agents' expectations in South Africa - Thobani Mlangeni; Eugene Msizi Buthelezi (Journal of Applied Economics, 2024)
This study employs a Vector Error Correction (VEC) model to investigate the dynamic relationship between changes in monetary policy and inflation expectations within various sectors. The analysis encompasses data from the financial, business, and trade union sectors, spanning the first quarter of 2000 to the fourth quarter of 2022. Results indicate that trade unions exhibit sensitivity to previous changes in the repo rate. In the long term, monetary policy influences inflation expectations within the financial sector. In contrast, elevated repo rates in the business sector correlate with diminished expectations, subsequently impacting wage dynamics. Granger causality tests establish a significant link between repo rate shifts and inflation expectations in the business and trade union sectors. The study advances the understanding of diverse sector responses to monetary policy's impact on inflation expectations, and implement sector-specific policy adjustments that consider the unique dynamics of each sector, ensuring a more targeted and effective response.
Keywords: 330; inflation expectations; Monetary policy